Competências dos orquestradores de ecossistemas de inovação nas cidades - Silva, Cassiane Marcieli Weide da (Universidade do Vale do Rio dos Sinos, 2023)
This dissertation addresses the competencies of ecosystem orchestrators in innovation within cities, recognizing the vital role of cities in economic, social, and environmental development. Understanding the competencies of these orchestrators is essential for improving strategic decision-making and constructing strategies for the evolution of innovation ecosystems. The study is based on a comprehensive review of existing literature, aiming to identify the skills, knowledge, and traits that make orchestrators effective in their roles. Although the literature has analyzed the dimensions, activities, and roles of orchestrators in promoting innovation ecosystems, the competencies required for this orchestration had not been explored in depth. Using a qualitative approach, the research identified the essential competencies for orchestrators in innovation ecosystems within cities, with a specific focus on the case of INOVA RS. The results emphasize the importance of key competencies, including a strategic and systemic vision, communication and collaboration skills, up-to-date knowledge of market and technology, adaptive and inclusive leadership, strategic partnership establishment, political influence, and impact evaluation with a focus on continuous improvement. These competencies are fundamental for creating an environment conducive to sustainable development and for addressing challenges within cities. The study underscores the need to understand and develop these competencies to drive innovation, thereby contributing to the construction of smarter, more resilient, and prosperous innovation ecosystems.
Keywords: Competências; Ecossistemas; Inovação; Orquestrador; Competences; Ecosystems; Innovation; Orchestrator; ACCNPQ::Ciências Sociais Aplicadas::Administração